Challenging The Status Quo: Anti-Establishment Rhetoric in Erdogan’s Official Discourse (2014 – 2020) - Ishpekova–Bratanova, Kalina (Research Papers, 2025)
The paper analyzes President Erdogan’s official statements using Fairclough’s three-dimensional Critical Discourse Analysis (CDA) model to explore how he legitimizes his rule and constructs Turkey’s image as a nation-state within the global order. He positions Turkey as a key player in addressing regional and global issues, portraying it as a tolerant nation capable of contributing to European and global stability. The paper argues that Erdogan’s discourse challenges existing power dynamics with the EU and Western institutions, promoting an inclusive vision of global cooperation and advocating for UN reform. Ultimately, Fairclough’s model reveals how Erdogan’s language constructs Turkey’s international image, critiquing global power structures while enhancing his domestic and international leadership standing.